Antibacterial, Antifungal, and Insecticidal Potentials of Oxalis corniculata and Its Isolated Compounds - Azizur Rehman; Ali Rehman; Ijaz Ahmad (International Journal of Analytical Chemistry)
Oxalis corniculata is a common medicinal plant widely used against numerous infectious diseases. The agrochemical potential of methanolic extract, n-hexane, chloroform, ethyl acetate, and n-butanol fractions were assessed to measure the antibacterial, antifungal, and insecticidal activities of the plant. The crude, chloroform, and n-butanol soluble fractions showed excellent activities against Escherichia coli, Shigella dysenteriae, Salmonella typhi, and Bacillus subtilis but have no activity against Staphylococcus aureus. Similarly the crude, n-hexane, and chloroform fractions were also found to have significant activity against fungal strains including Fusarium solani, Aspergillus flexneri, and Aspergillus flavus and have no activity against Aspergillus niger. Chemical pesticides have shown very good results at the beginning, but with the passage of time the need was realized to use the natural plant sources for the safe control of insects. The current study will provide minor contribution towards it. High mortality rate was recorded for the crude extract and chloroform fraction against Tribolium castaneum. The two isolated compounds 5-hydroxy-6,7,8,4′-tetramethoxyflavone (1) and 5,7,4′-trihydroxy-6,8-dimethoxyflavone (2) were evaluated for antibacterial, antifungal, and insecticidal activities. The results showed that compound 2 was more active than compound 1 against the tested bacterial strains and insects.